2017
DOI: 10.1016/j.copsyc.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Parenting in sport

Abstract: This paper provides a brief summary and commentary on the growing literature on parenting in sport, with a particular emphasis on literature from the last 2-3 years. Following a brief introduction overviewing the topic area, we firstly focus on the influence of parental involvement on children. Specifically, we examine the range of factors that influence children's perceptions of parental involvement and the consequences of different behaviors. Next we discuss the factors influencing parental involvement, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 46 publications
2
63
0
2
Order By: Relevance
“…Collectively, these studies have demonstrated the effectiveness and value of sport parent education programs. Such evidence plays an important role in helping to encourage the integration of evidence-based interventions within sports clubs, organizations and national governing bodies (Knight et al, 2017). However, these studies have also highlighted the significant cost, time, and expertise needed to plan and deliver evidence-based face-to-face education programs for service providers.…”
Section: Educating and Supporting Tennis Parents Using Web-based Delimentioning
confidence: 99%
“…Collectively, these studies have demonstrated the effectiveness and value of sport parent education programs. Such evidence plays an important role in helping to encourage the integration of evidence-based interventions within sports clubs, organizations and national governing bodies (Knight et al, 2017). However, these studies have also highlighted the significant cost, time, and expertise needed to plan and deliver evidence-based face-to-face education programs for service providers.…”
Section: Educating and Supporting Tennis Parents Using Web-based Delimentioning
confidence: 99%
“…In recent years, parenting in youth sport has become an important theme for talent and positive youth development (Knight, Berrow, & Harwood, 2017). Here, the findings contribute to knowledge of parental styles that safeguard athlete well-being (Harwood & Knight, 2015).…”
Section: Implications For Parenting In Sportmentioning
confidence: 72%
“…i.e. parents can influence both positive and negative (Holt & Knight, 2014;Knight, Berrow, & Harwood, 2017). Therefore, in the education of moral behaviour in athletes, the coach also has to have the ability to cooperate with the parents.…”
Section: Discussionmentioning
confidence: 99%